ASPEK PROSES DIAGENESIS TERHADAP SIFAT FISIK BATUPASIR FORMASI KEREK, DAERAH KALIPUTIH DAN SEKITARNYA, KECAMATAN SINGOROJO, KABUPATEN KENDAL, JAWA TENGAH - Vanny Hertanto Vahyu; Nugroho Hadi; Rachwibowo Prakosa (TEKNIK, 2012)
The sedimentary rock is formed and associated with the diagenesis processes, as all the physical, chemical, andbiological changes in the characteristics of a sediment accumulation from the time the grains are deposited untilthey are metamorphosed. This process is profoundly influence the characteristic of sedimentary rock, including thetexture, internal structure, mineral composition, cementation type, and pore space. Hence, it is important to knowor learn the stage of sandstone diagenesis, especially in the Kerek Formation to mark the correlation betweendiagenesis and physical properties of sandstone.The purpose of this research is to identify the stage of diagenetic processes, diagenetic environment, the type ofcementation, and the relationship between diagenetic stage and physical properties of sandstone. The methods usedin this research are survey method and data analysis method. The survey method includes the making of crosssectionalmeasured stratigraphy and data analysis method includes petrographic and scanning electron microscopy(SEM).The sedimentary structures found in the carbonate sandstones are burrows, convolute ripple lamination, gradedbedding, parallel lamination, cross lamination, current ripple lamination; which are features of turbidity deposition(Bouma sequence). Based on the petrography analysis results for sample P 01 and P 02 showed compaction,cementation, dissolution, and bioturbation, with a porosity value of 1 %. Sample P 03 showed compaction,cementation, dissolution, and bioturbation, with a porosity value of 7 %. Sample P 04 showed compaction,cementation, and dissolution, with a porosity value of 1 %. Sample P 06 showed compaction, cementation,dissolution and replacement, with a porosity value of 5 %. Sample P 07 showed compaction, and cementation, witha porosity value of 30 %. The Lithology type in the research area was Calcarenite with dominant shell fragment,the lithology names are Packed biomicrite (Folks, 1959; in Nichols, 2009), and Packstone (Dunham, 1962; inNichols, 2009). Carbonate sandstones predominantly feldspar and quartz minerals and the lihtology names areCarbonate quartz wackes (Pettijhon, 1975; in Nichols, 2009), and Carbonate feldspathic arenite (Pettijhon, 1975;in Nichols, 2009). There are three minerals type of cement showed in carbonate sandstones which are calcite,chlorite and pyrite cements.The results of this research indicate that the diagenesis stages of carbonate sandstones showed cementation,dissolution, replacement, bioturbation, and compaction processes, and the more stages of diagenesis that occurs incarbonate sandstones will result in reduced porosity and progressively up at for formation stratigraphy excelsiorsediment rock assess its porosity is equal to 1%, 5%, 7% and 15% respectively. The type of cement minerals in thecarbonate sandstone influence porosity, especially in carbonate sandstone which there are chlorite cement that havesmall porosity value of 1%, 5% and 7%. The environment of diagenesis in carbonate sandstones that is phreatic andburial experienced of eogenesis process, mesogenesis process and telogenesis process.